Smartphone to-do list application to improve workflow in an intensive care unit: A superiority quasi-experimental study. (April 2020) - Esposito, Mathieu; Rocq, Pierre-Louis; Novy, Emmanuel; Remen, Thomas; Losser, Marie-Reine; Guerci, Philippe; ,
Highlights: Optimal management of workflow is mandatory to provide reliable quality of care. Digital to-do lists improve comprehensiveness and bring visibility to workflow. Tasks-management through a mobile app enhance communication among medical staff. Thus, it increase young physicians' efficiency and may be used as an educational tool. Abstract: Background: Smartphone to-do list app was hypothesized to be more efficient than a paper-based list in the management of workflow and to provide additional benefits. Purpose: To analyze the impact of a mobile task-management application on the workflow of an ICU medical staff. Methods: Superiority by a margin test, quasi-experimental study comparing the use of a smartphone application versus standard practice regarding tasks management in an academic ICU. Superiority margin was set at 8 % based on a pilot study. During two periods of 20 working days each (October 2018 and January 2019), medical staff managed tasks with both methods on a weekly rotation basis. Primary outcome was the proportion of daily tasks completed. Secondary outcomes assessed users' satisfaction and the impact of the app in terms of changes in clinical practice. Results: 25 ICU physicians were enrolled. A total of 1983 tasks were recorded. The proportion of completed tasks per day was higher when using the smartphone app (99 % [96–100] versus 95 % [93–98] for the standard group, p = 0.006), but did not reach the superiority margin. Smartphone application was perceived as positive experience, as participants felt that they forgot fewer tasks (p = 0.02), were more aware of their progress on ongoing or remaining tasks (p = 0.03) and observed an improvement in communication among the medical staff (p = 0.03). Conclusion: This study failed to demonstrate the superiority of a smartphone app over paper-based lists regarding the proportion of daily tasks completed. However, positive feedback regarding the application was received from the medical staff.